Lung Quality and Utilization in Controlled Donation After Circulatory Determination of Death Within the United States. Issue 4 (4th February 2016) - Mooney, J. J.; Hedlin, H.; Mohabir, P. K.; Vazquez, R.; Nguyen, J.; Ha, R.; Chiu, P.; Patel, K.; Zamora, M. R.; Weill, D.; Nicolls, M. R.; Dhillon, G. S.
Abstract: Although controlled donation after circulatory determination of death (cDCDD) could increase the supply of donor lungs within the United States, the yield of lungs from cDCDD donors remains low compared with donation after neurologic determination of death (DNDD). To explore the reason for low lung yield from cDCDD donors, Scientific Registry of Transplant Recipient data were used to assess the impact of donor lung quality on cDCDD lung utilization by fitting a logistic regression model. The relationship between center volume and cDCDD use was assessed, and the distance between center and donor hospital was calculated by cDCDD status. Recipient survival was compared using a multivariable Cox regression model. Lung utilization was 2.1% for cDCDD donors and 21.4% for DNDD donors. Being a cDCDD donor decreased lung donation (adjusted odds ratio 0.101, 95% confidence interval [CI] 0.085–0.120). A minority of centers have performed cDCDD transplant, with higher volume centers generally performing more cDCDD transplants. There was no difference in center‐to‐donor distance or recipient survival (adjusted hazard ratio 1.03, 95% CI 0.78–1.37) between cDCDD and DNDD transplants. cDCDD lungs are underutilized compared with DNDD lungs after adjusting for lung quality. Increasing transplant center expertise and commitment to cDCDD lung procurement is needed to improve utilization. Abstract : After adjusting for donor lung quality, US transplant centers underutilize controlled donation after cardiac determination of death lungs compared to donation after neurologic determination of death lungs. See also Dark and Egan's editorial onpage 1047 .